Engineering of the alkyl chain branching point on a lactone polymer donor yields 17.81% efficiency. Issue 7 (4th February 2022) - Ou, Zongliang; Qin, Jianqiang; Jin, Ke; Zhang, Jianqi; Zhang, Lixiu; Yi, Chenyi; Jin, Zhiwen; Song, Qiuling; Sun, Kuan; Yang, Junliang; Xiao, Zuo; Ding, Liming
Abstract : Near-backbone manipulation of the alkyl chain branching point yields an efficient polymer donor L3 for organic solar cells. Abstract : Manipulation of the alkyl chain branching point has emerged as an effective strategy to enhance the performance of conjugated polymers in optoelectronic devices. In this work, an efficient lactone polymer donor L3 is developed via shifting the alkyl chain branching point from the β position to the γ position on the thiophene bridges of a known polymer L2. Such a near-backbone manipulation leads to enhanced backbone planarity, a smaller bandgap, varied energy levels, different packing behavior, improved hole mobility, reduced surface free energy and superior photovoltaic performance to L3. L3 demonstrates a power conversion efficiency of 17.81% (certified 17.1%) in ternary organic solar cells. L3 is among the few donors that can offer >17% certified efficiencies in organic solar cells to date.